Hubungan Durasi Penggunaan Ventilator Dengan Kejadian Ventilator Assocoates Pneumonia (VAP): Rapid Review - Fariz Jauhar Muslim (Edu Berjaya Publisher, 2025)
Background: Ventilator-associated pneumonia (VAP) is a common nosocomial infection in patients using mechanical ventilators, particularly those ventilated for more than 48 hours in intensive care units (ICUs). Prolonged ventilator use may impair airway defense mechanisms, increasing the risk of infection. Methods: This study employed a rapid review method by analyzing articles published between 2021 and 2025 obtained from Google Scholar using specific keywords related to ventilator duration and VAP incidence. A total of 659 articles were identified, with five studies meeting the inclusion criteria after a rigorous screening process. Results: Most of the reviewed studies showed a significant correlation between longer ventilator use and increased VAP incidence, especially after 48 hours of use. However, one study did not find a statistically significant association. Risk factors identified include impaired oral hygiene, sedation, and inadequate secretion management. Conclusion: The duration of mechanical ventilation, particularly exceeding 48 hours, is a contributing factor to VAP occurrence. Preventive efforts such as regular oral care, secretion management, hand hygiene, and timely weaning from ventilators are essential to reduce VAP risk in ICU patients. Future research is needed to explore other contributing factors and strengthen evidence-based prevention strategies.